Effects of Training on Running Cost and Aerobic Capacity in Individuals with Obesity - Castro, Eliane Aparecida [UNESP] (2023)
This study investigated running cost (C Run), peak oxygen consumption (V˙ O 2peak), and ventilatory threshold (VT 1) responses to exercise programs for individuals with obesity. Ninety-four individuals (38.2±7.7 years; 33.4±2.9 kg/m²) were assigned into strength (n=24), endurance (n=26), combined (n=22), and physical activity (control, n=22) groups for 22 weeks, plus diet recommendation. The V˙ O 2peak, VT 1, and C Runwere assessed through a maximal incremental step test. The change of V˙ O 2peakin combined (9.9%) differed from the other groups, with lower values in women than men (0.7% vs. 6.2%). The VT 1change in combined (16.4%) differed from the strength (4.9%) and physical activity (1.2%) groups, with the change in endurance (12.7%) also being higher than the physical activity group. Only men in the combined group increased absolute V˙ O 2peak, while both sexes increased VT 1in the endurance and combined groups. No effects for groups and sex were significant for C Runin moderate (<VT 1) or high-intensity (>VT 1) running zones, despite C Runchanges in <VT 1and >VT 1zones correlated with the alterations of V˙ O 2peakand VT 1(r²=0.29-0.59). Therefore, moderate aerobic exercise stimulus is suitable for VT 1improvement in individuals with obesity, with the increase in C Runassociated to the chances of increasing V˙ O 2peakin men and when combining strength with aerobic exercises.